Effectiveness of Prior Learning Recognition (RPL) Program Management in Improving Student Competence - Neneng Sulastri; Rahul Khan (The International Journal of Education Management and Sociology, 2026)
This study aims to analyze the effectiveness of Prior Learning Recognition (RPL) program management in improving student competence within the context of higher education. RPL is an innovative approach that acknowledges learners’ prior knowledge, skills, and experiences obtained through formal, non-formal, and informal learning. This research employs a qualitative approach with a descriptive-analytical design, utilizing data collected through literature review and document analysis. The findings indicate that effective RPL program management significantly contributes to enhancing student competence by accelerating learning pathways, increasing learning motivation, and ensuring the relevance of education to labor market needs. Key factors influencing the success of RPL implementation include institutional commitment, clear assessment standards, qualified assessors, and adequate administrative systems. However, challenges remain, such as limited awareness, inconsistent implementation, and lack of standardized procedures across institutions. Therefore, strengthening management strategies, improving regulatory frameworks, and enhancing institutional capacity are essential to optimize the effectiveness of RPL programs in improving student competence and supporting lifelong learning.